Pengaruh Kemampuan Public Speaking Guru Dalam Mengajar Terhadap Kepuasan Siswa Dalam Proses Pembelajaran Siswa Kelas XII Di SMAN 1 Alas - Tri Putri Yanti; Lalu Ahmad Taubih (INDO PUBLISHING, 2026)
This study aims to analyze the influence of teachers' public speaking skills on the learning satisfaction of 12th-grade students at SMAN 1 Alas. Using a quantitative approach with a survey design, the research involved 142 respondents selected thru the Simple Random Sampling technique from a total population of 219 students. Data analysis was conducted using SPSS 27. The test results show that all instruments are valid and reliable. The resulting simple linear regression equation is Y = 12.957 + 0.106X, indicating a positive relationship between the two variables. The hypothesis test (t-test) proves that the teacher's public speaking ability has a positive and significant effect on student satisfaction, with a calculated t-value (2.067) > table t-value (1.977) and significance 0.041 < 0.05. Specifically, the teacher's public speaking ability contributes 12% to student satisfaction, while the remaining 88% is influenced by other factors outside the study. These findings affirm that the teacher's verbal, vocal, and visual communication skills play a crucial role in creating an effective learning process and enhancing student satisfaction.